INOVASI SOFA YANG DIPADUKAN DENGAN RAK BUKU - Jati Widagdo (SULUH: Jurnal Seni Desain Budaya, 2019)
The existing sofa has a function only as a means to sit back and relax.When users sit reading newspapers, books, magazines or novels, people sitting on the sofa often stand up from their seats just to change feathers or reading, most people are sitting reading lazy to do it, because it is in a comfortable position. Likewise with bookshelves, most of the shapes are large and difficult and less mobile so that more people place them in corners of the room which are quite difficult to reach The development of the sofa is increasingly diverse, as now the sofa is no longer just a comfortable sitting facility but also functions as a furniture to decorate the room, one of which is a reading sofa, designed as a means of sitting while displaying other functions, namely the existence of a place to put books and magazines .A sofa that is equipped with a bookshelf is a collaboration between a sofa and a bookshelf where bookshelves are placed on both sides of the sofa which allows users to reach it easier. This design also has another function, namely the footrests that have been installed with the gas spring hydraulic system to increase sitting comfort.